An investigation into the extent to which grade 12 Mechanical Technology (MT) curriculum practices relate to the Green Economy: A case study of two Eastern Cape technical high schools - Mkaza, Mcebisi W (Rhodes University, Faculty of Education, Department of Education)
South Africa's transition towards a green economy presents opportunities to create resourceful jobs that promote sustainable living in the long term. The country's educational sector is mandated to integrate a green economy component in curricula from primary schools to tertiary levels. However, green jobs within such an economy require green skills which are not necessarily being developed effectively through the school curriculum. This interpretive study investigated how curriculum practices in the Grade 12 Mechanical Technology (MT) stream offered by technical high schools prepare learners to participate in green economy opportunities in the Eastern Cape. Guided by Practice Architecture theory, the study analysed curriculum documents relevant to the Grade 12 MT stream. Teachers and past learners were interviewed to investigate the Cultural-Discursive, Material-Economic and Socio-Political arrangements that enable or constrain teachers in their intentions to prepare learners to participate in the green economy. Teachers' material-economic arrangements constrained teaching and learning within the school premises. Learners did not have exposure to real-life fieldwork or job shadowing. Inflexible and restrictive socio-political arrangements in most subjects of the MT stream also constrained green economy learning opportunities. This hindered diversified learning in some subjects. The research further revealed that there is a need for updated pedagogical practices that are aligned with current educational practices. The research found that teachers had very little understanding of the green economy and broader environmental content in their subjects. Consequently, successful implementation of environmental content could not be achieved. The research highlights the importance of advocating for the inclusion of green economy content in the curriculum practices of subjects in the Mechanical Technology stream. This could begin during teacher in-service training as this could enhance teachers' limited knowledge of environmental content. For practising teachers, workshops, seminars and possibly conferences are necessary to augment knowledge they have, including their awareness of local green economy opportunities in the Eastern Cape.
Keywords: Technology-- Study and teaching -- South Africa -- Eastern Cape; Environmental education -- South Africa -- Eastern Cape; Curriculum evaluation -- South Africa -- Eastern Cape; Teachers In-service training -- South Africa -- Eastern Cape; Mechanical Technology; Green Economy; Practice Architecture Theory